Molybdenum-based materials/carbon nanotubes nanocomposites prepared as thin and transparent films for aqueous K-ion batteries. (10th August 2021) - Schmidt, Ariane; Ramos, Maria K.; Ferreira, Caroline M.; Braz, Beatriz A.; Zarbin, Aldo J.G.
Highlights: Nanocomposites between molybdenum-based materials (MoS2, amorphous molybdenum sulfide and oxide) and carbon nanotubes prepared as thin films through the liquid-liquid interfacial route. Morphology and electrochemical properties of the nanocomposites are strongly dependent on the experimental parameters. Films used as thin, transparent, and efficient anodes for aqueous K-ion batteries with capacities up to 517 mAh g −1 . Abstract: Thin films of nanocomposites composed of different molybdenum-based materials and carbon nanotubes were prepared and their performance as anodes in aqueous potassium-ion batteries was verified. The films were obtained through an innovative methodology based on the liquid/liquid interfacial route in a single-step procedure, starting from carbon nanotubes dispersions in chloroform or toluene, and molybdenum disulfide (or a mixture of amorphous molybdenum oxide/sulfide) dispersed in acetonitrile/water. The samples were characterized using different spectroscopic, microscopic, and electrochemical techniques, and it was observed a strong correlation between morphology and electrochemical performance. Materials obtained from chloroform dispersion of carbon nanotubes present more effective and intimate interaction between the components, which improves the electrochemical response. All the nanocomposites showed a pseudo-capacitive behavior in an aqueous solution of KCl, with a particularly good specific capacity, allowing their application as anodes in K-ion batteries fully operating in water. The best sample showed a specific capacity of 517 mAh g −1 at 7 A g −1 with a recovery degree close to 100%. Graphical abstract: Image, graphical abstract